The Prevalence of Absolute and Functional Iron Deficiency Anemia in New Cases of Smear-positive Pulmonary Tuberculosis and Their Sputum Conversion Rate at the End of Intensive Tuberculosis Treatment Phase - Metanat, Maliheh; Mashhadi, Mohammad Ali; Alavi-Naini, Roya; Rezaie-Kahkhaie, Leli; Sepehri-Rad, Nahid; Afshari, Mahdi (Prague Medical Report, 2020)
About one third of the population is infected with tuberculosis (TB). On the other hand, iron deficiency is the most common micronutrient deficiency in the world. A number of studies have documented anemia in patients with TB, however, this study aimed to assess the prevalence of iron deficiency anemia (IDA) in patients with acid-fast bacilli (AFB) sputum smear-positive, and sputum conversion in these two groups of patients with absolute and functional IDA at the end of the second month of anti-TB therapy in Zahedan, Iran. The results of this study revealed that 91 out of 198 (45.9%) sputum positive pulmonary TB patients were anemic, and among those 72 (79.1%) had iron deficiency anemia. The overall prevalence of IDA in this study was 36.3%. In 72 patients with IDA, 54 (75%) had functional while the remainder had absolute IDA 18 (25%). Twenty-one out of 72 (29.2%) of patients with IDA remained sputum positive and among 126 non IDA patients 47 (37.3%) had positive sputum smear at the end of intensive TB treatment phase (p=0.278). Approximately, less than half of patients with tuberculosis had anemia among them 79% had iron deficiency anemia. The frequency of functional IDA was three times more than absolute IDA. There was no statistically significant difference in sputum conversion between two groups of IDA and non-IDA patients after intensive phase of anti-TB therapy.
Keywords: Antitubercular Agents; Prevalence; anemie z nedostatku železa; Tuberculosis, Pulmonary; Sputum; prevalence; sputum; Anemia, Iron-Deficiency; lidé; Írán; Iran; antituberkulotika; plicní tuberkulóza; Humans; Mycobacterium tuberculosis